South African Economic Development in SADC Sub-Regional Integration - Enaifoghe, Andrew O.; Adetiba, Toyin C. (Journal of Economics and Behavioral Studies, 2018)
Following the end of colonialism in the Southern African sub-region, the SADC has experienced a thorough rearrangement with South Africa as the front-runner as opposed to her pre-1994 stance on integration. African regional cooperation has nevertheless been revitalised in some ways as a result of the two major events which started in the beginning of the 1990s that include the abolition of the apartheid regime in South Africa, and the eventual stabilisation of both political and economic relationships in the Southern Africa sub-region. This study employs the use of content analyses to assess the position of South Africa investments in SADC. Through the use ofregional integration, the studyfurther examined various South Africa’s Key Economy Performance since 1994 which are the main contributing factors to South African economic growth; furthermore it looks at her material, commodity and political investment in the subregional integration process to determine if it serves as the strategy for National Economic Development for South Africa.The paper find out thatregardless of South Africa’s economic clout within the SADC region, its Foreign Direct Investment is predominantly from its investment and market penetration of Southern Africa region while maintaining constant economic growth.